Prevalence, Risk Factors, and Outcomes of Platelet Transfusion Refractoriness in Critically Ill Patients: A Retrospective Cohort Study - Saeed Arabi; Abdullah O. Almahayni; Abdulrahman A. Alomair; Emad M. Masuadi; Moussab Damlaj; Hasan M. Al-Dorzi (Critical Care Research and Practice)
Background. Refractoriness to platelet transfusion is an understudied phenomenon in critically ill patients. Our objective was to evaluate the prevalence, risk factors, and clinical outcomes of platelet refractoriness among patients in a tertiary-care intensive care unit (ICU). Methods. A retrospective cohort study included all patients (age >14 years) who were admitted to a tertiary-care medical-surgical ICU between 2011 and 2016 and received ≥2 platelet transfusions during their ICU stay. We calculated platelet increment (PI) and corrected count increment (CCI). Results. A total of 267 patients were enrolled in the study, collectively receiving 1357 transfusions with a median of 4.0 (interquartile range: 2.0, 6.0) transfusions per patient. The median pretransfusion platelet count was 31000.0 × 106/L (interquartile range: 16000.0, 50000.0). The median PI was 6000 × 106/L. The prevalence of platelet transfusion refractoriness was 54.8% based on PI < 10000 × 106/L and 57.0% based on CCI <5000. Patients admitted under hepatology/liver transplant had the highest rates of platelet refractoriness (69.6%), while those under general surgery had the lowest rate (43.2%). Younger age, nontrauma admission, and larger spleen size were associated with platelet refractoriness. Finally, refractoriness was associated with increased length of stay in the ICU (p = 0.02), but not with mortality. Conclusions. Platelet transfusion refractoriness was highly (>50%) prevalent in ICU patients. However, it was not associated with increased mortality.